Body fat percentage is associated with cardiometabolic dysregulation in BMI-defined normal weight subjects - Shea, J.L.; King, M.T.C.; Yi, Y.; Gulliver, W.; Sun, G. (Nutrition, metabolism, and cardiovascular diseases, 2012)
Nearly 25% of normal weight individuals display abnormal metabolic profiles associated with obesity. As a wide range in body fat percentage (%BF) exists for BMI-defined normal weight individuals, we investigated whether elevated %BF (determined using DXA) was associated with cardiometabolic dysregulation among 977 normal weight subjects (192 men, 785 women) from the Canadian province of Newfoundland and Labrador. BMI and %BF were measured after a 12-h fasting period. Cardiometabolic abnormalities considered included elevated triglyceride, glucose and hsCRP levels, decreased HDL cholesterol, insulin resistance, and hypertension. Subjects were classified as metabolically healthy (0 or 1 cardiometabolic abnormality) or abnormal (≥2 cardiometabolic abnormalities) and divided into sex-specific %BF tertiles as follows: low (≤15.2% men, ≤29.7% women), medium (15.3–20.7%% men, 29.8–34.9%% women) and high (≥20.8% men, ≥35.0% women). The prevalence of the metabolically abnormal phenotype was higher among medium and high %BF subjects (12.0% and 19.5%, respectively) compared to the low group (7.4%; p < 0.05). Furthermore, the odds of being metabolically abnormal were 1.61 (95% CI 0.94–2.77) for medium %BF subjects compared to the low group and nearly tripled for high %BF subjects (OR 2.73, 95% CI 1.63–4.86). ORs remained significant after further adjustment for waist circumference. Our findings indicate that those with elevated %BF are at increased risk of developing cardiometabolic disease despite having a normal BMI. Future development of adequate screening tools to identify these individuals is crucial to the prevention of obesity-associated disease.